1998
DOI: 10.3327/jnst.35.494
|View full text |Cite
|
Sign up to set email alerts
|

Melting Temperature of Irradiated Fast Reactor Mixed Oxide Fuels.

Abstract: The melting (solidus) temperatures of irradiated mixed oxide fuels were measured and the compositions of the fuels on the temperature measurement date were calculated. The fuels contained about 29wt% Pu initially and were irradiated up to 124GWd/t in the experimental fast reactor JOYO. A melting temperature correlation was obtained by an experimental regression analysis using 21 measurements:where Tm is the expected melting temperature (K), XI the plutonium fraction (Pu/(Pu+U)) and X z the americium fraction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…2) For evaluating the melting temperature lowering from stoichiometric MOX that would be accountable solely to soluble FPs, we derived the deviations T Sol.FP from the measured T meas shown by that calculated using T Sol.MOX of Eq. (2), T Sol.O/M of Eq.…”
Section: Influence Of Burnup On Melting Temperature: T Solfpmentioning
confidence: 99%
See 2 more Smart Citations
“…2) For evaluating the melting temperature lowering from stoichiometric MOX that would be accountable solely to soluble FPs, we derived the deviations T Sol.FP from the measured T meas shown by that calculated using T Sol.MOX of Eq. (2), T Sol.O/M of Eq.…”
Section: Influence Of Burnup On Melting Temperature: T Solfpmentioning
confidence: 99%
“…3). While melting temperature lowering accountable to the presence of soluble FPs cannot be explained simply on the basis of ideal solution model, 2) assuming a pseudoternary system UO 2 -PuO 2 -FPsO 2 , the values of T m (FPsO 2 ) and h f (FPsO 2 ) were derived by curve-fitting.…”
Section: Influence Of Burnup On Melting Temperature: T Solfpmentioning
confidence: 99%
See 1 more Smart Citation
“…1) While many reports have been published on the solidus temperature and on equations for deriving the solidus for irradiated MOX fuel, [2][3][4][5] the only study on measuring its liquidus is that reported by Reavis et al 6,7) The present study aims at filling this gap by deriving the liquidus temperature equation of irradiated MOX fuel using as basis the solidus temperature equation in various reported studies. [8][9][10][11][12][13][14][15] Derivation of the equation proceeded in three steps, making reference to published reports where available: (1) Derive the liquidus temperature equation for unirradiated stoichiometric MOX fuel [8][9][10] and evaluate liquidus temperature lowering brought by the presence of Am and by the alteration herewith of fuel stoichiometry (oxygen-to-metal ratio (O/M) ratio), applying the procedure adopted previously for deriving the solidus temperature equation.…”
mentioning
confidence: 96%
“…For example, changing oxygen potential and increasing burnup can cause transition between groups (2) and (3), and between groups (1) and (3). Since soluble FPs tend to reduce the melting temperature, the oxides dissolved in the matrix, group (1), cause the greatest effect on the melting temperature; the other two precipitates, groups (2) and (3), have small effects on the matrix. The gases and other volatile FPs, group (4), have little or no effect on melting temperature.…”
Section: Introductionmentioning
confidence: 99%